Fibers as carriers of microbial particles - Rafał L. Górny; Anna Ławniczek-Wałczyk; Agata Stobnicka; Małgorzata Gołofit-Szymczak; Marcin Cyprowski (Nofer Institute of Occupational Medicine, 2015)
Background: The aim of the study was to assess the ability of natural, synthetic and semi-synthetic fibers to transport microbial particles. Material and Methods: The simultaneously settled dust and aerosol sampling was carried out in 3 industrial facilities processing natural (cotton, silk, flax, hemp), synthetic (polyamide, polyester, polyacrylonitrile, polypropylene) and semi-synthetic (viscose) fibrous materials; 2 stables where horses and sheep were bred; 4 homes where dogs or cats were kept and 1 zoo lion pavilion. All samples were laboratory analyzed for their microbiological purity. The isolated strains were qualitatively identified. To identify the structure and arrangement of fibers that may support transport of microbial particles, a scanning electron microscopy analysis was performed. Results: Both settled and airborne fibers transported analogous microorganisms. All synthetic, semi-synthetic and silk fibers, present as separated threads with smooth surface, were free from microbial contamination. Natural fibers with loose packing and rough surface (e.g., wool, horse hair), sheaf packing and septated surface (e.g., flax, hemp) or present as twisted ribbons with corrugated surface (cotton) were able to carry up to 9×105 cfu/g aerobic bacteria, 3.4×104 cfu/g anaerobic bacteria and 6.3×104 cfu/g of fungi, including pathogenic strains classified by Directive 2000/54/EC in hazard group 2. Conclusions: As plant and animal fibers are contaminated with a significant number of microorganisms, including pathogens, all of them should be mechanically eliminated from the environment. In factories, if the manufacturing process allows, they should be replaced by synthetic or semi-synthetic fibers. To avoid unwanted exposure to harmful microbial agents on fibers, the containment measures that efficiently limit their presence and dissemination in both occupational and non-occupational environments should be introduced. Med Pr 2015;66(4):511-523